Adult Obstructive Sleep Apnea: A Practical Guide for the Allergist (Canadian Allergy & Immunology Today, 2024)
Obstructive sleep apnea (OSA) is a common sleep disorder, affecting 15-30% of males and 10-15% of females in North America. OSA is characterized by the recurrent obstruction of the upper airway during sleep resulting in apneas and hypopneas. OSA can be diagnosed using a home sleep apnea test (i.e., a level 3 sleep study) or a polysomnogram (PSG) (i.e., a level 1 study or PSG) in a supervised sleep laboratory which quantifies the number of apneas and hypopneas per hour using the apnea-hypopnea index (AHI). In broad terms, the diagnosis is made when an individual with symptoms or cardiac risk factors has an AHI of ≥5, or an asymptomatic individual has an AHI of ≥15. Continuous Positive Airway Pressure (CPAP) is considered the first-line treatment of OSA. Other treatment options include an oral appliance called a mandibular advancement device, or multilevel surgery of the upper airway, especially uvulopalatopharyngoplasty (UPPP). Herein we review OSA in the context of conditions commonly observed in the allergy clinic, namely asthma, chronic rhinosinusitis, rhinitis, and contact dermatitis.